Analysis of Public Service Quality in the Regional Technical Implementation Unit (UPTD) of Cigalontang Community Health Center, Cigalontang District, Tasikmalaya Regency - Sartika; Agus Fatah Hidayat; M. Ikrar Budijaya (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2026)
Public service is a vital component of governance, ensuring that the basic needs of the community are met effectively and with high quality. This study aims to analyze the quality of public service at the Cigalontang Community Health Center (UPTD), Tasikmalaya Regency, prompted by the gap between the services provided by the health center and the community’s expectations. The focus of this study is based on six dimensions of service quality according to Prof. Dr. Lijan Poltak Sinambela, namely transparency, accountability, conditionality, participation, equality of rights, and the balance of rights and obligations. The method used in this study is a qualitative approach with data collection techniques through observation, documentation study, and in-depth direct interviews with 14 informants consisting of service providers and recipients. Data analysis techniques include data reduction, data presentation, and drawing conclusions. The research findings indicate that, in general, the quality of public services at the Cigalontang Community Health Center (UPTD Puskesmas) is quite good and in accordance with Standard Operating Procedures (SOPs), particularly regarding accountability, responsiveness, and the fulfillment of equal rights without discrimination. However, several challenges remain, such as a lack of transparency regarding service procedures, limited facilities and infrastructure—such as waiting rooms and parking spaces—as well as inconsistent staff attitudes in providing courteous service. The study’s conclusions indicate that while minimum service standards have been met, improvement efforts are still necessary, particularly in enhancing facilities and infrastructure and optimizing the dissemination of information to the public to maximize service satisfaction.